2008
DOI: 10.1016/j.paid.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of race and racial priming on self-report of contamination anxiety

Abstract: African Americans show unusually high endorsement rates on self-report measures of contamination anxiety. The purpose of this study was to replicate this finding in a nationally representative sample and conduct a randomized experiment to determine the effect of salience of race as a causal factor. Black and White participants were given contamination items from two popular measures of obsessive-compulsive disorder, half prior to being primed about ethnic identity and half after being primed, via the administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 21 publications
0
50
1
Order By: Relevance
“…Contrary to some previous studies carried out in adults (Himle et al, 2008;Williams et al, 2005Williams et al, , 2008, our White and non-White samples did not differ substantially in their clinical presentation. Specifically, our minority children and adolescents did not display a later age of onset of the OCD and did not endorse more contamination concerns, as reported previously in African American and Asian American samples (Himle et al, 2008;Wheaton et al, 2013;Williams et al, 2005Williams et al, , 2008. Only three individual symptoms from the C-YBOCS-SC showed borderline significant between-group differences, and, of those, only the fear of not saying the right thing tended to be more prevalent among the non-White group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to some previous studies carried out in adults (Himle et al, 2008;Williams et al, 2005Williams et al, , 2008, our White and non-White samples did not differ substantially in their clinical presentation. Specifically, our minority children and adolescents did not display a later age of onset of the OCD and did not endorse more contamination concerns, as reported previously in African American and Asian American samples (Himle et al, 2008;Wheaton et al, 2013;Williams et al, 2005Williams et al, , 2008. Only three individual symptoms from the C-YBOCS-SC showed borderline significant between-group differences, and, of those, only the fear of not saying the right thing tended to be more prevalent among the non-White group.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, this symptom was also found to be elevated in an adult sample of African Americans with OCD in the study by Williams, Elstein, Buckner, Abelson, and Himle (2012). The authors of that study suggested that the obsessive need to be perfectly understood could be connected to minority status; according to the authors, African Americans may exhibit fears of appearing unintelligent, resulting in stereotype compensation -an intentional effort to present one's self in a counter-stereotypical manner (Williams et al, 2008;Williams, Elstein, et al, 2012). It may be that certain, but not all, ethnic groups (e.g., African Americans) may differ in some respects.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Williams, Turkheimer, Schmidt, and Oltmanns (2005) studied a large internet sample using the Padua Inventory (Sanavio, 1988), another self-report measure of OCD symptoms, and found a similar pattern of high African American endorsement of contamination items: non-clinical African American participants scored as highly as participants reporting a diagnosis of OCD. Extension of this research suggests that these differences are partially explained by cultural factors, including geography and whether the participants were primed with information that triggered thoughts about their ethnic identity before contamination measures were administered (Williams, Turkheimer, Magee, & Guterbock, 2008). Similarly, Williams and Turkheimer (2007) found that ethnic differences in contamination anxiety reflected varied cultural attitudes toward grooming and housekeeping as opposed to actual differences in the severity of psychopathology.…”
Section: Introductionmentioning
confidence: 82%
“…R. Johnson et al, 2007;Monnier et al, 2002;Scott et al, 2002;M. T. Williams & Turkheimer, 2007;M. T. Williams et al, 2008), and treatment outcome (M. M. Carter et al, 2003;Friedman et al, 2003;Zoellner et al, 1999).…”
Section: Learning History and Contextual Variablesmentioning
confidence: 99%